Pengembangan UMKM Naik Kelas Berbasis Manajemen Usaha Pada Kelompok Usaha Kuliner di Desa Ladang Bambu Kecamatan Medan Tuntungan - Yusrita; Zenni Riana; M. Endang Asmara; Muhammad Prasetyo Wibowo; Cornelia Ivani (JPM: Jurnal Pengabdian Masyarakat, 2023)
The function and role of SMEs is currently felt to be very important. Aside from being a source of livelihood for many people, it also provides direct employment for the majority of the population. As a small business group, SMEs are always trapped in the problem of limited capital, inaccurate distribution, inefficient financial management, lack of innovation, not yet maximizing online marketing, bookkeeping is still manual, time management, does not have permits as an effort to improve the capabilities of small businesses in the context of expanding its role in the national economy, a series of integrated and sustainable development is needed to overcome various problems. External factors consist of government policies in the public sector, social, cultural and economic aspects, as well as aspects of the role of related institutions. MSME actors in the Kampung Bambu Village, Medan Tuntungan District, are housewives who use their time at home to generate income to supplement their family's income. There are 47 business actors in the Kebun Bambu Village who become a business group. Judging from the age at which they started doing business, the business actors in the bamboo farming village should have graduated, considering that this business group is part of the local government program, namely One Kelurahan, One Entrepreneurship Center.